THE PHILIPPINES’ MARITIME CLAIMS OVER SABAH: A MALAYSIAN PERSPECTIVE - Yusof, Salma; Md Saman, Mazura; Taib, Khairul Nizam (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This paper analyses the Philippines’ maritime claims concerning Sabah within the framework of the 1982 United Nations Convention on the Law of the Sea (1982 UNCLOS). Employing a qualitative methodology, the study relies on secondary data sources including legislations, treaties, law reports, government documents and journal articles relevant to the issue. It assesses the Philippines’ legal capacity to assert maritime zones in lights of its unresolved territorial claim to Sabah. The analysis also highlights the relationship between territorial sovereignty and maritime rights, particularly in relation to Malaysia’s existing maritime jurisdiction over the areas. By evaluating these competing claims, the paper assesses the legal viability of the Philippines’ position and its broader implications for regional stability and international dispute resolution. The findings indicate that the Philippines' claims present a complex historical, legal and geopolitical aspects that influences regional security and diplomatic relations. While both countries have expressed a commitment to resolving the dispute peacefully, the path forward remains uncertain. Continued dialogue and adherence to international legal frameworks will be essential in addressing this longstanding territorial issue.